1994
DOI: 10.1152/ajprenal.1994.267.6.f1052
|View full text |Cite
|
Sign up to set email alerts
|

Role of CD11a and CD11b in ischemic acute renal failure in rats

Abstract: Leukocytes, particularly neutrophils, have been implicated in ischemic-reperfusion organ injury (IRI). However, their role in kidney IRI is controversial. Leukocytes express the adhesion molecules CD11/CD18 on their surface, which mediate many functions that can lead to tissue damage. To determine the role of CD11a and CD11b in IRI in the kidney, uninephrectomized Sprague-Dawley rats were pretreated with monoclonal antibodies (MAbs) directed against CD11a and CD11b or control MAbs. The serum creatinine (SCr), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
0
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(95 citation statements)
references
References 0 publications
3
89
0
3
Order By: Relevance
“…Although L-selectin has been shown to be important in I/R injury in different tissues, such as the liver (24), skeletal muscle (25), and heart muscle (26), its role in renal I/R injury is controversial (15). Integrins implicated in the inflammatory response to renal ischemia are the ␤2 integrins CD11a and CD11b (27,28), which are known to bind to intercellular adhesion molecule-1 on the endothelium. This binding may ultimately result in transmigration of the leukocyte across the endothelial monolayer and the underlying extracellular matrix into the renal interstitium.…”
Section: Discussionmentioning
confidence: 99%
“…Although L-selectin has been shown to be important in I/R injury in different tissues, such as the liver (24), skeletal muscle (25), and heart muscle (26), its role in renal I/R injury is controversial (15). Integrins implicated in the inflammatory response to renal ischemia are the ␤2 integrins CD11a and CD11b (27,28), which are known to bind to intercellular adhesion molecule-1 on the endothelium. This binding may ultimately result in transmigration of the leukocyte across the endothelial monolayer and the underlying extracellular matrix into the renal interstitium.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is well demonstrated that leukocyte adhesion molecule blockade plays a tissue protective role in IRI in muscle and heart, it is still a matter of controversy in the kidney. CD11/CD18 and intercellular adhesion molecule-1 blockade are usually protective in experimental renal IRI (9,12). In contrast, induction of systemic neutropenia and selectin function blockade do not have a protective effect, suggesting a neutrophil-independent mechanism for renal protection (6).…”
Section: Discussionmentioning
confidence: 99%
“…Leukocyte adhesion molecules seem to facilitate polymorphonuclear neutrophils recruitment during reperfusion, being implicated as mediators of renal IRI (5,6). Complementary studies using mAb, antisense oligonucleotides, or gene "knockout" indicate that blockade of ␤2 integrins and/or intercellular adhesion molecule-1 attenuates IRI in some experimental models (7)(8)(9)(10)(11)(12)(13). Furthermore, it was proposed recently that T cells might also mediate IRI through the interaction with renal tubular epithelial cells (14).…”
mentioning
confidence: 99%
“…ICAM-1 knockout mice appeared resistant to acute renal ischemic injury (89). Similarly, anti-CD11a and antiCD11b antibodies decreased injury after experimental renal ischemia in the rat (94). Furthermore, mice deficient for the Src-family kinases Hck and Fgr, required for integrin signal transduction, were resistant to the lethal effects of LPS-injection and had a marked reduction in renal damage (95).…”
Section: Inhibition Of Leukocyte Adhesionmentioning
confidence: 99%